Intolerance of uncertainty and maladaptive perfectionism as maintenance factors for eating disorders and obsessive‐compulsive disorder symptoms. (21st November 2020) - Williams, Brenna M.; Levinson, Cheri A.
Abstract: Objective: Eating disorders (EDs) are highly comorbid with obsessive‐compulsive disorder (OCD). In order to develop treatments which better address commonly comorbid ED and OCD symptoms, it is important to identify potential shared mechanisms. Two potential shared mechanisms are maladaptive perfectionism and intolerance of uncertainty (IU). We aimed to assess how maladaptive perfectionism and IU may contribute to the maintenance of ED and OCD symptoms in individuals with EDs. Methods: In the current study ( N = 168 individuals with an ED), we analysed cross‐sectional and prospective path models of maladaptive perfectionism and IU as maintenance factors of ED and OCD symptoms. Results: We found that IU was associated with both ED and OCD symptoms, and maladaptive perfectionism was associated with ED symptoms. We also found that maladaptive perfectionism and IU prospectively predicted OCD symptoms, but not ED symptoms. Conclusions: Overall, these findings suggest that it may be beneficial to target both maladaptive perfectionism and IU in individuals with a current ED diagnosis in order to prevent the development of OCD symptoms. Highlights: Intolerance of uncertainty is a shared correlate of eating disorder (ED) and obsessive‐compulsive disorder (OCD) symptoms. We did not find support for maladaptive perfectionism as a maintenance factor for EDs. Maladaptive perfectionism and intolerance of uncertainty may promote OCD symptoms in individuals with an ED.